2019
DOI: 10.31234/osf.io/he6j2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different laterality indexes are poorly correlated with one another but consistently show the tendency of males and females to be more left- and right- lateralised, respectively

Abstract: Handedness is assessed primarily as a binary trait on the basis of the preferred hand for writing. At population level, about 90% people prefer using the right. Handedness can also be assessed as a continuous trait with laterality indexes, but these are not time and cost effective, and are not routinely collected. Here, we assessed the relationship of writing hand preference with four laterality indexes derived from measures of dexterity (pegboard task, marking squares and sorting matches) and strength (grip s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
2
3
0
Order By: Relevance
“…This is consistent with the overall correlation of .40~.50, indicating that the two measures do not map exactly on to each other. These results also concur with the aforementioned recent study conducted on UK children showing poor correlations across different handedness measures [53]. Our bivariate genetic modelling analysis further revealed that a model with one latent genetic factor did not fit the data.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with the overall correlation of .40~.50, indicating that the two measures do not map exactly on to each other. These results also concur with the aforementioned recent study conducted on UK children showing poor correlations across different handedness measures [53]. Our bivariate genetic modelling analysis further revealed that a model with one latent genetic factor did not fit the data.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also found a discrepancy between boys and girls in the singleton sample on their pegboard performance scores, continuous or categorical. Though our sample is too small for the detection of significant sex effect, the pattern is consistent with a recent study in UK which found females tend to be more right lateralized and males are more left lateralized for PegQ [53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, preference is correlated with measures of relative hand skill with an estimated correlation of magnitude of .62 to .73 (Todor & Doane, 1977) or more recent estimates of .50 to .57 (Triggs et al, 2000), while Corey, Hurley, and Foundas (2001) found that in more than 90% of cases preference-based groups corresponded to groups based on relative hand skill. A recent study also showed that the correlation between hand preference and relative hand skill highly depends on which test is used to assess relative hand skill (Buenaventura Castillo, Lynch, & Paracchini, 2019, preprint). The authors assessed the relationship of hand preference with measures of relative hand skill (pegboard task, marking squares, and sorting matches) and relative hand strength (grip strength).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, to come to a preferably differentiated picture of an individual’s lateralization, studies may combine different measures of self-reported hand preference and measures of hand skill as well as measures of other forms of functional asymmetries (e.g., language lateralization). This notion may be especially relevant considering that different performance measures of handedness (the Pegboard task amongst them) have been revealed to show only small correlations among each other and may reflect distinct dimensions of asymmetries 47 . Undoubtedly, a comprehensive assessment of functional asymmetries—which we refer to as deep phenotyping—may not be applicable for larger-scale studies.…”
Section: Introductionmentioning
confidence: 99%